Gestational inhalation of nanoparticles alters placental glucose transporter expression and increases glucose flux in rats - Talia N. Seymore; Sara Hoffmann; Pedro Louro; Carol Gardner; Michael J. Goedken; Phoebe A. Stapleton (Toxicology and Applied Pharmacology, 2026)

Polystyrene nanoplastics disrupt mouse placenta development in a sex-dependent manner - Hanin Alahmadi; Allison Harbolic; Christopher De Oliveira-Cordova; Raulle Reynolds; Michelle Jojy; Courtney Potts; Sofia Doan; Tanvi Mathur; Mohammad Saiful Islam; Melisa J. Andrade; Quinton Smith; Phoebe A. Stapleton; et al. (Reproductive Toxicology, 2026)

Erratum to ‘Gestational inhalation of nanoparticles alters placental glucose transporter expression and increases glucose flux in rats’ [Toxicol. Appl. Pharmacol. 515 (2026) 117996] - Talia N. Seymore; Sara Hoffmann; Pedro Louro; Carol Gardner; Michael J. Goedken; Phoebe A. Stapleton (Toxicology and Applied Pharmacology, 2026)

Analysis of Human Placental Tissues Using Gas Chromatography High Resolution Accurate Mass Spectrometry to Characterize Exposure to a Range of Semivolatile Organic Compounds - Michelle Misselwitz; Nicholas J. Herkert; P. Lee Ferguson; Heather M. Stapleton (Exposure and Health, 2026)

Triphenyl phosphate promotes lipid accumulation in human mesenchymal stem cells through metabolic stress pathways - M. C. Gronske; W. Stutts; D. Jima; J. Palumbo; H. M. Stapleton; S. W. Kullman (Archives of Toxicology, 2026)
Organophosphate esters (OPEs), used as both plasticizers and flame retardants, are increasingly recognized for their potential to disrupt cellular homeostasis and emerging evidence indicates their ability to induce metabolic stress in diverse biological systems. This study investigated the impact of Triphenyl Phosphate (TPhP) on human mesenchymal stem cell (hMSC) differentiation and cell stress. hMSCs were treated with DMSO (vehicle control), 10 µM rosiglitazone (a PPARγ agonist), or 25 µM TPhP for 14–21 days. Following treatment, cells were stained to assess nuclear integrity, lipid accumulation, and mineralization. Immunocytochemistry (ICC) for osteogenic and adipogenic markers was used to determine whether TPhP promotes adipogenesis under osteogenic conditions. TPhP exposure led to significant lipid accumulation without activation of adipogenic differentiation programs and markedly reduced mineralization. In particular, co-treatment with PPARγ inhibitors did not mitigate lipid accumulation or modulate the expression of adipogenic regulators. Gene expression analysis following TPhP exposures revealed upregulation of pathways involved in lipid biogenesis, triglyceride synthesis, phospholipid metabolism and endoplasmic reticulum (ER) stress, with minimal changes to classical adipogenic markers. These findings indicate that TPhP disrupts the metabolic balance between osteogenesis and lipid metabolism, with the potential to promote ectopic lipid deposition within the bone forming environment. This dysregulation is relevant for the development of metabolic disorders, including obesity, type 2 diabetes, and metabolic bone diseases, including osteoporosis.

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Gestational exposure to micro and nanoplastics differentially impacts cardiac development and function in male and female rats throughout the lifespan - Chelsea M. Cary; Samantha Adams; Gina M. Moreno; Talia N. Seymore; Marianne Polunas; Michael J. Goedken; Xiang Wang; Edward J. Yurkow; Phoebe A. Stapleton (Toxicology and Applied Pharmacology, 2025)

Habitat fidelity in hawksbill sea turtles - Andrew S. Maurer; Julia A. Horrocks; Claudio Bellini; Karen L. Eckert; Alexandra L. Fireman; Mariana M. P. B. Fuentes; Barry Krueger; Kathryn E. Levasseur; Maria A. Marcovaldi; Renata M. A. Ramos; Seth P. Stapleton; Hannah B. Vander Zanden; et al. (Ecology, 2025)
Climate change is altering habitat suitability and driving shifts in species distributions. To understand potential responses by mobile animals, it is essential to assess levels of plasticity in habitat use, ranging from transience to long‐term fidelity. Here, we evaluate the fidelity of hawksbill sea turtles ( Eretmochelys imbricata ) to habitats used while foraging (our primary focus), migrating, and nesting. After satellite tracking 17 adult females from three Western Atlantic nesting areas, we then re‐tracked them in a subsequent year. Of 15 turtles with sufficient data to assess interannual foraging area fidelity, 14 returned to the same home range, exhibiting overlap between successive 50% utilization distributions (UDs); the 15th individual shifted

Sublingual caffeine delivery via oral spray does not accelerate blood caffeine increase compared to ingestion of caffeinated beverages - Devin G. McCarthy; Rileigh K. Stapleton; Rachel M. Handy; Samuel Amanual; Samantha Tsioros; Philip J. Millar; Jamie F. Burr (European Journal of Applied Physiology, 2025)

A global assessment of microplastic abundance and characteristics on marine turtle nesting beaches - Zara L.R. Botterell; Jed Ardren; Elly Dove; Ellen McArthur; David S. Addison; Oyeronke M. Adegbile; Pierre Didier Agamboue; Andrews Agyekumhene; Phil Allman; Alexandra Alterman; Adren Anderson; Theresa Arenholz; et al. (Marine Pollution Bulletin, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Associations of environmental chemical exposures measured in personal silicone wristbands with sociodemographic factors, COVID-19 restrictions, and child respiratory health - Brennan H. Baker; Drew B. Day; Marnie F. Hazlehurst; Nicholas J. Herkert; Heather M. Stapleton; Sheela Sathyanarayana (Environmental Research, 2024)

Long Amplicon Nanopore Sequencing for Dual-Typing RdRp and VP1 Genes of Norovirus Genogroups I and II in Wastewater - G. Scott; D. Ryder; M. Buckley; R. Hill; S. Treagus; T. Stapleton; D. I. Walker; J. Lowther; F. M. Batista (Food and Environmental Virology, 2024)
Noroviruses (NoVs) are the leading cause of non-bacterial gastroenteritis with societal costs of US$60.3 billion per annum. Development of a long amplicon nanopore-based method for dual-typing the RNA-dependent RNA polymerase ( RdRp ) and major structural protein ( VP1 ) regions from a single RNA fragment could improve existing norovirus typing methods. Application to wastewater-based epidemiology (WBE) and environmental testing could enable the discovery of novel types and improve outbreak tracking and source apportionment. Here, we have developed such a method with a consensus-based bioinformatics pipeline and optimised reverse transcription (RT) and PCR procedures. Inhibitor removal and LunaScript® RT gave robust amplification of the ≈ 1000 bp RdRP + VP1 amplicon for both the GI and GII PCR assays. Platinum™ Taq polymerase showed good sensitivity and reduced levels non-specific amplification (NSA) when compared to other polymerases. Optimised PCR annealing temperatures significantly reduced NSA (51.3 and 42.4% for GI and GII), increased yield (86.5% for GII) and increased taxa richness (57.7%) for GII. Analysis of three NoV positive faecal samples showed 100% nucleotide similarity with Sanger sequencing. Eight GI genotypes, 11 polymerase types (p-types) and 13 combinations were detected in wastewater along with 4 GII genotypes, 4 p-types and 8 combinations; highlighting the diversity of norovirus taxa present in wastewater in England. The most common genotypes detected in clinical samples were all detected in wastewater while we also frequently detected several GI genotypes not reported in the clinical data. Application of this method into a WBE scheme, therefore, may allow for more accurate measurement of norovirus diversity within the population.

Identification of micro- and nanoplastic particles in postnatal sprague-dawley rat offspring after maternal inhalation exposure throughout gestation - Gina M. Moreno; Tanisha Brunson-Malone; Samantha Adams; Calla Nguyen; Talia N. Seymore; Chelsea M. Cary; Marianne Polunas; Michael J. Goedken; Phoebe A. Stapleton (Science of The Total Environment, 2024)

Ecological niche use varies with sea turtle reproductive age - Alexandra L. Fireman; Seth P. Stapleton; Hannah Vander Zanden; Dong Liang; Ryan J. Woodland (Marine Biology, 2024)

Advancing Understanding of Chemical Exposures and Maternal-child Health Through the U.S. Environmental Influences on Child Health Outcomes (ECHO) Program: A Scoping Review - Emily S. Barrett; Jennifer L. Ames; Stephanie M. Eick; Alicia K. Peterson; Zorimar Rivera-Núñez; Anne P. Starling; Jessie P. Buckley; Barbara O‟Brien; Lisa Peterson; Patrick Parsons; Kannan Kurunthacalam; Manish Arora; et al. (Current Environmental Health Reports, 2024)
Purpose of Review Environmental chemical exposures may disrupt child development, with long-lasting health impacts. To date, U.S. studies of early environmental exposures have been limited in size and diversity, hindering power and generalizability. With harmonized data from over 60,000 participants representing 69 pregnancy cohorts, the National Institutes of Health’s Environmental influences on Child Health Outcomes (ECHO) Program is the largest study of U.S. children’s health. Here, we: (1) review ECHO-wide studies of chemical exposures and maternal-child health; and (2) outline opportunities for future research using ECHO data. Recent Findings As of early 2024, in addition to over 200 single-cohort (or award) papers on chemical exposures supported by ECHO, ten collaborative multi-cohort papers have been made possible by ECHO data harmonization and new data collection. Multi-cohort papers have examined prenatal exposure to per- and polyfluoroalkyl substances (PFAS), phthalates, phenols and parabens, organophosphate esters (OPEs), metals, melamine and aromatic amines, and emerging contaminants. They have primarily focused on describing patterns of maternal exposure or examining associations with maternal and infant outcomes; fewer studies have examined later child outcomes (e.g., autism) although follow up of enrolled ECHO children continues. The NICHD’s Data and Specimen Hub (DASH) database houses extensive ECHO data including over 470,000 chemical assay results and complementary data on priority outcome areas (pre, peri-, and postnatal, airway, obesity, neurodevelopment, and positive health), making it a rich resource for future analyses. Summary ECHO’s extensive data repository, including biomarkers of chemical exposures, can be used to advance our understanding of environmental influences on children’s health. Although few published studies have capitalized on these unique harmonized data to date, many analyses are underway with data now widely available.

Long-Term Follow-Up of Cerebral Aneurysms Completely Occluded at 6 Months After Intervention with the Woven EndoBridge (WEB) Device: a Retrospective Multicenter Observational Study - Kareem El Naamani; Panagiotis Mastorakos; Nimer Adeeb; Mathews Lan; James Castiglione; Omaditya Khanna; Jose Danilo Bengzon Diestro; Rachel M. McLellan; Mahmoud Dibas; Justin E. Vranic; Assala Aslan; Hugo H. Cuellar-Saenz; et al. (Translational Stroke Research, 2024)

Evaluating the generation of microplastics from an unlikely source: The unintentional consequence of the current plastic recycling process - Michael J. Stapleton; Ashley J. Ansari; Aziz Ahmed; Faisal I. Hai (Science of The Total Environment, 2023)

Correction to: The Woven EndoBridge (WEB) Device for the Treatment of Intracranial Aneurysms: Ten Years of Lessons Learned and Adjustments in Practice from the WorldWideWEB Consortium - Adam A. Dmytriw; Mahmoud Dibas; Sherief Ghozy; Nimer Adeeb; Jose Danilo Bengzon Diestro; Kevin Phan; Hugo H. Cuellar-Saenz; Ahmad Sweid; Sovann V. Lay; Adrien Guenego; Leonardo Renieri; Ali Al Balushi; et al. (Translational Stroke Research, 2023)

Characterizing azobenzene disperse dyes and related compounds in house dust and their correlations with other organic contaminant classes - Kirsten E. Overdahl; Christopher D. Kassotis; Kate Hoffman; Gordon J. Getzinger; Allison Phillips; Stephanie Hammel; Heather M. Stapleton; P. Lee Ferguson (Environmental Pollution, 2023)

Change in the chemical, mechanical and physical properties of plastics due to UVA degradation in different water matrices: A study on the recyclability of littered plastics - Michael J. Stapleton; Ashley J. Ansari; Aziz Ahmed; Faisal I. Hai (Environmental Pollution, 2023)

Renaming of the genus Flavivirus to Orthoflavivirus and extension of binomial species names within the family Flaviviridae - Thomas S. Postler; Martin Beer; Bradley J. Blitvich; Jens Bukh; Xavier de Lamballerie; J. Felix Drexler; Allison Imrie; Amit Kapoor; Galina G. Karganova; Philippe Lemey; Volker Lohmann; Peter Simmonds; et al. (Archives of Virology, 2023)

The Woven EndoBridge (WEB) Device for the Treatment of Intracranial Aneurysms: Ten Years of Lessons Learned and Adjustments in Practice from the WorldWideWEB Consortium - Adam A. Dmytriw; Mahmoud Dibas; Sherief Ghozy; Nimer Adeeb; Jose Danilo Bengzon Diestro; Kevin Phan; Hugo H. Cuellar-Saenz; Ahmad Sweid; Sovann V. Lay; Adrien Guenego; Leonardo Renieri; Ali Al Balushi; et al. (Translational Stroke Research, 2023)

Barriers and Facilitators to Stool-Based Screening for Colorectal Cancer Among Black Louisville Residents - Aaron J. Kruse-Diehr; Derek Cegelka; Elizabeth Holtsclaw; Jerod Stapleton; Camille Burnett; Rose Wood; Carlee Combs; Lovoria B. Williams (Journal of Cancer Education, 2023)

Wastewater-based monitoring reveals geospatial-temporal trends for antibiotic-resistant pathogens in a large urban community - Zillur Rahman; Weijia Liu; Lara Stapleton; Nikki Kenters; Dewa A.P. Rasmika Dewi; Ori Gudes; Helen Ziochos; Stuart J. Khan; Kaye Power; Mary-Louise McLaws; Torsten Thomas (Environmental Pollution, 2023)

Antibiotic sorption onto microplastics in water: A critical review of the factors, mechanisms and implications - Michael J. Stapleton; Ashley J. Ansari; Faisal I. Hai (Water Research, 2023)

Mosquito control opportunities amid regulations within the tidal marshes of the San Francisco Bay Area - Erika B. Castillo; Ryan J. Clausnitzer; Eric J. Haas-Stapleton (Wetlands Ecology and Management, 2022)

An on-ice aerial survey of the Kane Basin polar bear (Ursus maritimus) subpopulation - Øystein Wiig; Stephen N. Atkinson; Erik W. Born; Seth Stapleton; Todd Arnold; Markus Dyck; Kristin L. Laidre; Nicholas J. Lunn; Eric V. Regehr (Polar Biology, 2022)
There is an imminent need to collect information on distribution and abundance of polar bears ( Ursus maritimus ) to understand how they are affected by the ongoing decrease in Arctic sea ice. The Kane Basin (KB) subpopulation is a group of high-latitude polar bears that ranges between High Arctic Canada and NW Greenland around and north of the North Water polynya (NOW). We conducted a line transect distance sampling aerial survey of KB polar bears during 28 April–12 May 2014. A total of 4160 linear kilometers were flown in a helicopter over fast ice in the fjords and over offshore pack ice between 76° 50′ and 80° N′. Using a mark-recapture distance sampling protocol, the estimated abundance was 190 bears (95% lognormal CI: 87–411; CV 39%). This estimate is likely negatively biased to an unknown degree because the offshore sectors of the NOW with much open water were not surveyed because of logistical and safety reasons. Our study demonstrated that aerial surveys may be a feasible method for obtaining abundance estimates for small subpopulations of polar bears.

Body size and digestive system shape resource selection by ungulates: A cross‐taxa test of the forage maturation hypothesis - Saeideh Esmaeili; Brett R. Jesmer; Shannon E. Albeke; Ellen O. Aikens; Kathryn A. Schoenecker; Sarah R. B. King; Briana Abrahms; Bayarbaatar Buuveibaatar; Jeffrey L. Beck; Randall B. Boone; Francesca Cagnacci; Simon Chamaillé‐Jammes; et al. (Ecology Letters, 2021)
The forage maturation hypothesis (FMH) states that energy intake for ungulates is maximised when forage biomass is at intermediate levels. Nevertheless, metabolic allometry and different digestive systems suggest that resource selection should vary across ungulate species. By combining GPS relocations with remotely sensed data on forage characteristics and surface water, we quantified the effect of body size and digestive system in determining movements of 30 populations of hindgut fermenters (equids) and ruminants across biomes. Selection for intermediate forage biomass was negatively related to body size, regardless of digestive system. Selection for proximity to surface water was stronger for equids relative to ruminants, regardless of body size. To be more generalisable, we suggest that the FMH explicitly incorporate contingencies in body size and digestive system, with small‐bodied ruminants selecting more strongly for potential energy intake, and hindgut fermenters selecting more strongly for surface water.

Assessment of the Applicability of Capsid-Integrity Assays for Detecting Infectious Norovirus Inactivated by Heat or UV Irradiation - David I. Walker; Lisa J. Cross; Tina A. Stapleton; Connaire L. Jenkins; David N. Lees; James A. Lowther (Food and Environmental Virology, 2019)

Use of F-Specific RNA Bacteriophage to Estimate Infectious Norovirus Levels in Oysters - J. A. Lowther; L. Cross; T. Stapleton; N. E. Gustar; D. I. Walker; M. Sills; S. Treagus; V. Pollington; D. N. Lees (Food and Environmental Virology, 2019)

Advantages of melodic over rhythmic movement sonification in bimanual motor skill learning - J. F. Dyer; P. Stapleton; M. W. M. Rodger (Experimental Brain Research, 2017)

Feasibility of solar tents for inactivating weedy plant propagative material - James J. Stapleton (Journal of Pest Science, 2012)

Creative Solution for Implementation of Experiential, Competency-Based Palliative Care Training for Internal Medicine Residents - Douglas D. Ross; Deborah W. Shpritz; Susan D. Wolfsthal; Ann B. Zimrin; Timothy J. Keay; Hong-Bin Fang; Carl A. Schuetz; Laura M. Stapleton; David E. Weissman (Journal of Cancer Education, 2011)

Deleterious activity of cultivated grasses (Poaceae) and residues on soilborne fungal, nematode and weed pests - James J. Stapleton; Charles G. Summers; Jeffrey P. Mitchell; Timothy S. Prather (Phytoparasitica, 2010)

Polybrominated Diphenyl Ethers in American Eels (Anguilla rostrata) from the Delaware River, USA - J. T. F. Ashley; D. Libero; E. Halscheid; L. Zaoudeh; H. M. Stapleton (Bulletin of Environmental Contamination and Toxicology, 2007)

Female tree swallows (Tachycineta bicolor) increase offspring heterozygosity through extrapair mating - Mary K. Stapleton; Oddmund Kleven; Jan T. Lifjeld; Raleigh J. Robertson (Behavioral Ecology and Sociobiology, 2007)

Effects of temperature variation on suicide in five U.S. counties, 1991–2001 - P. G. Dixon; A. N. McDonald; K. N. Scheitlin; J. E. Stapleton; J. S. Allen; W. M. Carter; M. R. Holley; D. D. Inman; J. B. Roberts (International Journal of Biometeorology, 2007)

Retrospective analysis of 49 cases of brain abscess and review of the literature - J. Carpenter; S. Stapleton; R. Holliman (European Journal of Clinical Microbiology & Infectious Diseases, 2007)

Irradiance-induced changes in the photobiology of Halophila johnsonii - J. I. Kunzelman; M. J. Durako; W. J. Kenworthy; A. Stapleton; J. L. C. Wright (Marine Biology, 2005)

The fate of 15 N added to high Arctic tundra to mimic increased inputs of atmospheric nitrogen released from a melting snowpack - A. M. Tye; S. D. Young; N. M. J. Crout; H. M. West; L. M. Stapleton; P. R. Poulton; J. Laybourn‐Parry (Global Change Biology, 2005)
Increases in the long‐range aerial transport of reactive N species from low to high latitudes will lead to increased accumulation in the Arctic snowpack, followed by release during the early summer thaw. We followed the release of simulated snowpack N, and its subsequent fate over three growing seasons, on two contrasting high Arctic tundra types on Spitsbergen (79°N). Applications of 15 N (99 atom%) at 0.1 and 0.5 g N m −2 were made immediately after snowmelt in 2001 as either Na 15 NO 3 or 15 NH 4 Cl. These applications are approximately 1 × and 5 × the yearly atmospheric deposition rates. The vegetation at the principal experimental site was dominated by bryophytes and Salix polaris while at the second site, vegetation included bryophytes, graminoids and lichens. Audits of the applied 15 N were undertaken, over two or three growing seasons, by determining the amounts of labeled N in the soil (0–3 and 3–10 cm), soil microbial biomass and different vegetation fractions. Initial partitioning of the 15 N at the first sampling time showed that ∼60% of the applied 15 N was recovered in soil, litter and plants, regardless of N form or application rate, indicating that rapid immobilization into organic forms had occurred at both sites. Substantial incorporation of the 15 N was found in the microbial biomass in the humus layer and in the bryophyte and lichen fractions. After initial partitioning there appeared to be little change in the total 15 N recovered over the following two or three seasons in each of the sampled fractions, indicating highly conservative N retention. The most obvious transfer of 15 N, following assimilation, was from the microbial biomass into stable forms of humus, with an apparent half‐life of just over 1 year. At the principal site the microbial biomass and vascular plants were found to immobilize the greatest proportion of 15 N compared with their total N concentration. In the more diverse tundra of the second site, lichen species and graminoids competed effectively for 15 NH 4 ‐N and 15 NO 3 ‐N, respectively. Results suggest that Arctic tundra habitats have a considerable capacity to immobilize additional inorganic N released from the snow pack. However, with 40% of the applied 15 N apparently lost there is potential for N enrichment in the surrounding fjordal systems during the spring thaw.

Comparing Polybrominated Diphenyl Ether and Polychlorinated Biphenyl Bioaccumulation in a Food Web in Grand Traverse Bay, Lake Michigan - H. M. Stapleton; J. E. Baker (Archives of Environmental Contamination and Toxicology, 2003)

Sedimentary Nonylphenol Contamination in an Urbanized, Industrialized Segment of the Delaware River Estuary, USA - J. T. F. Ashley; A. Moore; H. M. Stapleton; D. J. Velinsky; M. P. Wilhelm (Bulletin of Environmental Contamination and Toxicology, 2003)

Abstracts of presentations on selected topics at the xlvth international plant protection congress (IPPC) July 25–30, 1999 - G. Theodoridis; D. Shaner; J. Townson; J. Kemp; P. Cory; D. Bartlett; P. Sutton; D. Collins; R. Wiehert; S. O. Duke; F. E. Dayan; J. G. Romagni; et al. (Phytoparasitica, 2000)

Nicotine availability from Eclipse tobacco-heating cigarette - J. A. Stapleton; Michael A. H. Russell; Gay Sutherland; Colin Feyerabend (Psychopharmacology, 1998)

Improvement of soil solarization with volatile compounds generated from organic Amendments - A. Gamliel; J. J. Stapleton (Phytoparasitica, 1997)

Bioavailability of sorbed- and separate-phase chemicals - James R. Mihelcic; Donald R. Lueking; Robert J. Mitzell; J. Mark Stapleton (Biodegradation, 1993)